Análisis del proceso de producción de la piña para aumentar la exportación del Ecuador hacia el mercado español, aplicando las normas de calidad (iso 14001 y eurogap) a partir del año 2009 - Avelino Quimi, Wendy (2009)
The pineapple MD2 has a great international demand, due to its good flavour. However, according to the Ecuadorian exportations, the pineapple MD2 has been exported to Spain in a few quantities. The Spain market demands to follow the GLOBALGAP (EUROGAP) RULES, because it permits to have more control about all the products that they import and will be commercialized. In Ecuador, there are exporters who can not maintain its quality standard at the moment that the pineapple is exported, for this reason the Ecuadorian exportations are not so much toward Spain market. To change this situation, it’s necessary to implement new market strategies that include more quality control. The product analysis and the Ecuadorian pineapple MD2 marketing are important to obtain a high quality pineapple, in this way the producer and export companies could have the standard warranty certificate. An increase in the pineapple exportation will generate more incomes and more sources of jobs in Ecuador.